Radiological Protection Management: software implementation in a hospital in south Brazil - ANDREA HUHN; GERUSA RIBEIRO; DAIANE CRISTINI BARBOSA DE SOUZA; TIANA DE GUSMAO; KASSIA ROSANGELA PAZ DE MACEDO; RODRIGO D AGOSTINI DERECH; BEATRIZ PATRÍCIA VIRISSIMO DOS SANTOS; MARIA ALICE P. D’AMOREIRA (Brazilian Journal of Radiation Sciences, 2024)
The exacerbated increase in the use of ionizing radiation to obtain images, and the risks and standards that exist to preserve the health of those who use it, are not properly taken into account when carrying out radiodiagnostic examinations. The professionals who work in these environments play a decisive role in the performance of their numerous activities within radiodiagnostic services, bearing in mind that any dose of radiation is associated with a probability of biological effects occurring, no matter how low that dose may be. Thus, the aim of building a software program was to optimize the work of the multiprofessional and interdisciplinary team in radiodiagnostic services, in the management of radiological protection. This is a methodological and quasi-experimental study carried out in a university hospital in southern Brazil, intentionally chosen because it has a Radiological Protection Committee. This research design was adopted for the development of technological production, in this case software for managing radiological protection. The study was carried out in the radiological protection sector of the radiology department of a university hospital in southern Brazil. The results showed that the software, called SisPRad - Management System for Radiological Protection, is a tool that helps the service's multi-professional and interdisciplinary team in terms of managing radiological protection. Finally, it aims to ensure the safety of professionals working in the service and its users, as well as reducing repetition of activities at management level, and can be adapted for other institutions. The computer registration number 512019002125-8 was obtained from the National Institute of Industrial Property for the first version of the software and the registration number 512023003116-0 for its second version.